Desmoplastic myxoid tumor, SMARCB1-mutant: clinical, histopathological and molecular characterization of a pineal region tumor encountered in adolescents and adults - Thomas, Christian; Wefers, Annika K.; Bens, Susanne; Nemes, Karolina; Agaimy, Abbas; Oyen, Florian; Vogelgesang, Silke; Rodriguez, Fausto J.; Brett, Francesca M.; McLendon, Roger; Bodi, Istvan; Burel-Vandenbos, Fanny; et al. (Acta neuropathologica, 2020)
Atypical teratoid/rhabdoid tumor (ATRT) is a highly malignant brain tumor predominantly occurring in infants. Mutations of the SMARCB1 gene are the characteristic genetic lesion. SMARCB1-mutant tumors in adolescents and adults are rare and may show uncommon histopathological and clinical features. Here we report seven SMARCB1-deficient intracranial tumors sharing distinct clinical, histopathological and molecular features. Median age of the four females and three males was 40 years (range 15-61 years). All tumors were located in the pineal region. Histopathologically, these tumors displayed spindled and epithelioid cells embedded in a desmoplastic stroma alternating with a variable extent of a loose myxoid matrix. All cases showed loss of nuclear SMARCB1/INI1 protein expression, expression of EMA and CD34 was frequent and the Ki67/MIB1 proliferation index was low in the majority of cases (median 3%). Three cases displayed heterozygous SMARCB1 deletions and two cases a homozygous SMARCB1 deletion. On sequencing, one tumor showed a 2 bp deletion in exon 4 (c.369_370del) and one a short duplication in exon 3 (c.237_276dup) both resulting in frameshift mutations. Most DNA methylation profiles were not classifiable using the Heidelberg Brain Tumor Classifier (version v11b4). By unsupervised t-SNE analysis and hierarchical clustering analysis, however, all tumors grouped closely together and showed similarities with ATRT-MYC. After a median observation period of 48 months, three patients were alive with stable disease, whereas one patient experienced tumor progression and three patients had succumbed to disease. In conclusion, our series represents an entity with distinct clinical, histopathological and molecular features showing epigenetic similarities with ATRT-MYC. We propose the designation desmoplastic myxoid tumor (DMT), SMARCB1-mutant, for these tumors.